Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran Matematika: Application of Cooperative Learning Model Type Numbered Head Together to Improve Learning Outcomes in Mathematics Subjects - Irman, Irman (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The learning outcomes of grade VI students in Mathematics subjects at SDN Megamendung 01 Megamendung District are still very low. This is what motivates researchers to conduct research. The purpose of this research is to improve the learning outcomes of students in Mathematics subjects, by using the Numbered Head Together Type Cooperative learning model. This research was conducted collaboratively with two cycles. The subjects of this research were VI grade students of Megamendung 01 State Elementary School, Megamendung District, Bogor Regency, totaling 43 students with a composition of 21 female students and 22 male students. The research was conducted in the even semester of the 2023-2024 academic year. The results showed that the percentage value of learning outcomes in the pre-cycle was 47%, the first cycle was 70% and the second cycle was 91%, this means that there is an increase or improvement in the learning outcomes of students in each cycle. This study concludes that the application of the Numbered Head Together Cooperative Learning Model can improve learning outcomes in Mathematics subjects for grade VI students at Megamendung 01 State Elementary School, Megamendung District, Bogor Regency. In addition, the application of the Numbered Head Together Cooperative Learning Model can increase activeness, cooperation, and participation in the learning process.